Study of Trace Elements and Role of Zinc Supplementation in Children with Idiopathic Intractable Epilepsy - Elshorbagy, Hatem H.; Bassiouny, Mohammed M.; Kamal, Naglaa M.; Azab, Ahmed A.; Ghoneim, Ibrahim A. (Journal of Pediatric Epilepsy, 2016)
Background Trace elements have physiological effects on neuronal excitability that may play a role in the etiology of intractable epilepsy. The aim was to evaluate the possible associations between some trace elements and idiopathic intractable epilepsy in children, and also the role of zinc supplementation in reduction of seizures in such patients.Materials and Methods Our study was designed as a case-control study with 80 idiopathic epileptic patients between the ages of 10 months and 14 years enrolled in the study, 45 intractable to treatment (Group I) and 35 controlled by treatment (Group II). Serum levels of selenium, zinc, and copper were measured with atomic absorption spectrophotometer. Group I patients were subdivided according to zinc supplementation into two subgroups. Group IA included 31 epileptic patients with refractory response and oral zinc supplementation for 4 months and Group IB included 14 epileptic patients with refractory response and without zinc supplementation with continuous follow-up of patients for further 6 months for evaluation of seizure recurrence.Results We found that Group I patients had significantly lower levels of serum Se and Zn compared with those of Group II patients (p < 0.05). Serum copper levels were not significantly lower in Group I than Group II. Zinc supplementation resulted in a significant reduction of seizure in Group I A compared with Group IB. Recurrence of seizure activity after discontinuation of zinc supplementation was significant in Group IA (p < 0.01).Conclusions We found significantly lower serum levels of zinc and selenium in patients with intractable epilepsy as compared to the controlled epilepsy group. Zinc supplementation had a significant role in reduction of seizures in such patients.
Keywords: trace elements; intractable epilepsy; controlled epilepsy; zinc supplementation